Electronically tunable sinusoidal oscillator circuit with current and voltage outputs - Ayten, U. E.; Sagbas, M.; Sedef, H. (TAYLOR & FRANCIS LTD, 2012)
A new circuit configuration for the realisation of an electronically tunable sinusoidal oscillator is presented. The proposed circuit uses only one current backward transconductance amplifier (CBTA), two grounded capacitors and one resistor. Using current controlled CBTA (CC-CBTA) instead of the CBTA, the resistor can be completely removed. It has also current-mode (CM) and voltage-mode (VM) outputs, simultaneously. The workability of the proposed structure has been demonstrated by both simulation and experimental results.
Keywords: sinusoidal oscillator; current backward transconductance amplifier; current-mode; voltage-mode; electronic tunability; SINGLE; FILTERS; Engineering